2014
DOI: 10.1016/j.apsusc.2014.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent silicon nanocrystals produced by near-infrared nanosecond pulsed laser ablation in water

Abstract: a b s t r a c tWe report the investigation of luminescent nanoparticles produced by ns pulsed Nd:YAG laser ablation of silicon in water. Combined characterization by AFM and IR techniques proves that these nanoparticles have a mean size of ∼3 nm and a core-shell structure consisting of a Si-nanocrystal surrounded by an oxide layer. Time resolved luminescence spectra evidence visible and UV emissions; a band around 1.9 eV originates from Si-nanocrystals, while two bands centered at 2.7 eV and 4.4 eV are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…Considering the fact that HF removes the SiO x layer by chemical etching, the reduction in the rst peak (426 nm) can show us that this peak is mainly due to oxide related defects at Si/SiO x interface. This conclusion is in agreement with some of the previous studies where the blue emission is contributed to the defects at Si/SiO x interface 29,36 rather than direct recombination in ultra-small (<5 nm) Si nanocrystals (due to quantum connement). These studies show that the blue emission from Si nanocrystals is occurred at energy of 2.7 eV and this is mainly due to a forbidden triplet-tosinglet transition inside the SiO x shell layer.…”
Section: Resultssupporting
confidence: 93%
“…Considering the fact that HF removes the SiO x layer by chemical etching, the reduction in the rst peak (426 nm) can show us that this peak is mainly due to oxide related defects at Si/SiO x interface. This conclusion is in agreement with some of the previous studies where the blue emission is contributed to the defects at Si/SiO x interface 29,36 rather than direct recombination in ultra-small (<5 nm) Si nanocrystals (due to quantum connement). These studies show that the blue emission from Si nanocrystals is occurred at energy of 2.7 eV and this is mainly due to a forbidden triplet-tosinglet transition inside the SiO x shell layer.…”
Section: Resultssupporting
confidence: 93%
“…In agreement with previous experiments [8], the colloidal solution produced by LA consists of nanoparticles with an average diameter of a few nanometers and containing Si-nc as demonstrated by the characteristic Raman line at 518 cm −1 . We measured the mass of this product after drying the solution; it is ∼2.2 mg.…”
Section: Resultssupporting
confidence: 92%
“…Laser ablation of silicon in liquid media offers the possibility of production of well dispersed colloidal SiNPs with unique surface characteristics such as oxide, hydroxyl and alkyl surface passivations [6][7][8][9][10]. It was shown that the SiNP powders that prepared by PLA in liquids and drying the host liquid media mainly have the same surface characteristics as those of the colloidal samples [6,36,39]. Indeed, during the ablation process in liquids, a reaction between the solvent molecules with high temperature and pressure laser induced plasma can result in formation of stable surface products on the nanoparticles [55].…”
Section: Resultsmentioning
confidence: 99%
“…Especially, it was shown that PLA of silicon in different solvents can result in production of colloidal silicon nanoparticles (SiNPs) with remarkable optical properties which are applicable in optoelectronics and medicine [5][6][7][8][9][10][11][12][13][14][15]. In recent years, nanoscale structure of silicon with novel optical properties have received much attention due to the wide range of applications in light emitting diodes [16][17][18], lasers [19,20] and sensors [21].…”
Section: Introductionmentioning
confidence: 99%